La gestion des peuplements forestiers touchés par les tempêtes de décembre 1999 : l’exemple de la forêt domaniale de Perche-Trappe (Orne) - Yves Petit-Berghem (Cybergeo, 2004)
The violent storms which occurred in the winter of 1999 (December 26th and 28th) severely hit French forests: 140 million m3 of timber were thrown to the ground, thus destroying a volume equivalent to an average 3 years of productivity. In Lower Nomandy, the Perche-Trappe forest was one of the most severely hit out of the whole French State forest network. It was the finest example of the oak-elm association in Normandy but it also had coniferous species, some of which were unable to resist wind-throw. Massive uprooting generated clearings in which new plant dynamics have manifested themselves. In order to assess the extent of these plant dynamics but also with a view to help regeneration and environmental conservation, the Perche Natural Regional Park placed an order with the scientific authority of the Géophen Research Center based in Caen University so that this one carries out an ecological diagnosis in pieces of conifers. This assessment showed strong vegetational regeneration but it also showed that the soil could be impoverished due to compaction. This paper deals with the question of landscape restoration and the means and methods upon which environmental conservation can be based. As users of the land, local farmers could be actively involved in the conservation process, once they have been made aware of the importance of environmental protection.